Celastrol at the obesity–cancer interface: critical appraisal of molecular mechanisms, preclinical evidence, and translational barriers - Asma B. Omer; Muhammad Afzal; Shakir Saleem; Mohd Masih Uzzaman Khan; A. Rekha; Rajat Sharma (Molecular Biology Reports, 2026)

Next-generation hybrid membranes integrating MXene and MOF architectures for energy-efficient water treatment - Saleem Raza; Luqman Ali; Muhammad Usman Hameed; Sidra Khalid; Sundas Shoukat; Mamuna Ahmad; Liguo Shen; Ghafar Ali; Imran Shakir (Desalination, 2026)

Electrochemical CO2 reduction technologies: A comprehensive review of system design strategies and operational challenges for industrial scale-up - Muhammad Shakir Hussain; Chirong Sun; Jaehyuk Lim; Jaehoon Kim (Journal of Environmental Chemical Engineering, 2026)

Recent advances in electrochemical ion separation: Materials, mechanisms and sustainable applications for water and resource recovery - Luqman Ali; Abdul Majid Khan; Muhammad Usman Hameed; Saleem Raza; Liguo Shen; Imran Shakir; Muhammad Hafeez (Desalination, 2026)

Gastrodia elata Blume (Tianma) extract mitigates simulated microgravity–induced oxidative stress and enhance learning and memory in Caenorhabditis elegans - Muhammad Zulqarnain Shakir; Inam Ullah; Muhammad Wasim Usmani; Jiang Ning; Jixian Liu; Xuchen Zhou; Yufen Zhao; Guanghua Lu; Qiaobei Du; Huabiao Chen; Muhammad Imran; Muhammad Ashraf; et al. (Life Sciences in Space Research, 2026)

Impact of Land Use Change on Water Quality: Toward Sustainable Ecosystem Management in the Nenggiri River Basin - Ismafatin Nabilah Ismail; Mohd Khairul Amri Kamarudin; Mohamad Hafis Amat Simin; Asmawi Ibrahim; Wan Nor Azilawanie Tun Ismail; Ahmad Shakir Mohd Saudi; Mohd Ekhwan Toriman; Sunardi Sunardi; Firdaus Muhammad-Sukki (Water, Air, & Soil Pollution, 2026)

Neuropathic pain in traumatic brain injury: consequences, mechanisms, and therapeutic avenues - Faaizah Fazal; Nargis Bano; Sameera Khan; Shakir Ahamad; Syed Muhammad Sarosh Ghalib; Supriyo Saha; Nawab John Dar; Shahnawaz A. Bhat (Inflammopharmacology, 2026)

Dietary sodium propionate enhances growth performance, digestive enzymes, haematology and immunity in Wallago attu - Ayesha Tanveer; Noor Khan; Mahroze Fatima; Hafiz Abdullah Shakir; Ayesha Khizar; Syed Zakir Hussain Shah; Laiba Kareem; Saba Aftab; Malik Muhammad Ramzan; Ahmed Mustafa; Simon John Davies (Journal of Fish Biology, 2026)
Sodium propionate (SP), a short‐chain fatty acid, has been widely used as a feed additive to improve fish growth and health status. The current experiment was designed to investigate the effects of dietary SP on growth, enzymatic activities, haematology and immune status of Wallago attu . Fingerlings (initial weight = 8.80 ± 0.58 g) were fed with graded levels of SP comprising 0.0, 0.5, 1.0, 2.0, 4.0 and 8.0 g/kg levels for 60 days in triplicate glass aquaria (89 × 58 × 61 cm [length × width × depth]). The results showed significant ( p W. attu fingerlings when fed with graded levels of SP. In conclusion, the SP supplementation in W. attu showed best results ranged between 2 and 4 g/kg level by improving fish health and growth performance.

Advances in functional carbon composites for electrochemical energy conversion and catalysis: Design strategies, mechanisms and future prospects - Luqman Ali; Muhammad Usman Hameed; Xingfen Huang; Saleem Raza; Abdul Majid Khan; Mashkoor Ahmad; Akif Safeen; Imran Shakir (Journal of Environmental Chemical Engineering, 2026)

Neurobiological and neurophysiological impacts of real spaceflight and simulated microgravity on C. elegans: a comprehensive review - Muhammad Zulqarnain Shakir; Ning Wang; Muhammad Wasim Usmani; Inam Ullah; Jixian Liu; Xuchen Zhou; Yufen Zhao; Qiaobei Du; Huabiao Chen; Jiang Ning; Xinmin Liu (Life Sciences in Space Research, 2026)

Molecular detection of Toxoplasma gondii in Amblyomma gervaisi ticks infesting monitor lizards (Varanus bengalensis) - Muhammad Naeem; Muhammad Ammar Ameen; Hafiza Misbah Munir; Huma Fatima; Shakir Ullah; Hira Muqaddas; Kasim Sakran Abass; Adil Khan; Furhan Iqbal (Experimental and Applied Acarology, 2026)

Integrated Assessment of Water Quality and Sediment Load Production in River and Lake Basins: A Comprehensive Analysis for Environmental Management and Community Health - Mohd Khairul Amri Kamarudin; Noorjima Abd Wahab; Mohd Ekhwan Toriman; Firdaus Muhammad-Sukki; Ahmad Shakir Mohd Saudi; Fazureen Azaman (Water, Air, & Soil Pollution, 2026)
River and lake basins can be regarded as primary water sources, providing communities with a variety of services, including food supplies, flora and fauna habitats, and household uses. To evaluate the state of the water quality, particularly in the lake basin, sedimentation issues and water quality status are considered. The Kenyir Lake Basin's health was tracked in this study using the Water Quality Index (WQI), JPS River Index (JRI), and Sediment Load (SL) production. Determining and analysing the trends in water quantity and quality throughout the Kenyir Lake Basin was the goal of this study. For the purpose of this study, samples were taken at 21 different locations around the lake basin in the wet (November), dry (September), and normal (July) seasons. Six WQI parameters, four JRI parameters, and three SL production parameters have been chosen. In the linear connection to forecast WQI, JRI, and SL, several important variables serve as inputs. The key parameters were identified for each index, such as pH, Dissolved Oxygen (DO), and ammoniacal nitrogen (NH₃-N) which were critical for the WQI; specific flow was essential for the JRI; and Total Suspended Solids (TSS) were important for the sediment load (SL) production analysis. Furthermore, the Hazard Quotient (HQ) was subsequently calculated to conduct a preliminary assessment of the potential health risks associated with metal exposure. The elements' HQ ingestion values were discovered to be in the following order: Arsenic (As) > Cadmium (Cd) > Copper (Cu) > Cobalt (Co) > Chromium (Cr) > Nickel (Ni) > Zinc (Zn) > Plumbum (Pb); all averaged HQ values were less than 1, suggesting that there was little to no health risk from the metals in question. Overall, the WQI results indicate that the basin's water quality is generally Class I to Class II, with WQI values of at least 60% across all sampling points. Linear relationship analysis identified DO as the most critical parameter influencing the WQI across all seasons (contributing up to 64.40% in the dry season), followed by ammoniacal nitrate (AN) and Biochemical Oxygen Demand (BOD). The human health risk assessment revealed that the non-carcinogenic risk from metal exposure (As, Cd, Cu, Co, Cr, Ni, Zn, Pb) was negligible, as all averaged HQ values were less than 1. However, the carcinogenic risks associated with exposure to As and Cr were identified as high. Although the water quality has not reached a critical threshold, unregulated anthropogenic activities pose a substantial and intensifying threat to the ecosystem and local communities. These findings necessitate a more systematic environmental management approach to mitigate future degradation. Apart from the river, anthropogenic activities such as sand mining, tourism, agriculture, and municipal wastewater treatment were assessed using secondary data obtained from land use records, environmental monitoring reports, and official discharge statistics. Analysis of these data revealed that such activities play a substantial role in contributing to the concentration of polluting elements in the river water. Although the current level of water quality and quantity degradation in the Kenyir Lake Basin has not yet reached a critical threshold, the potential adverse impacts on the ecosystem and local communities are likely to intensify if these anthropogenic pressures remain unregulated.

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

Integrating Conventional and machine learning approaches with seismic inversion for optimized porosity estimation in heterogeneous siliciclastic rocks - Muyyassar Hussain; Urooj Shakir; Zohaib Naseer; Muhammad Raiees Amjad; Farooq Arshad; Muhammad Kamal; Ahmed E. Radwan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Nonlinear shock and solitary wave structures in nonplanar non-Maxwellian plasmas - Shakir Ullah; Abdullah Alshehab; Muhammad Shohaib; Huda Alfannakh; Najeh Rekik (Advances in Space Research, 2026)

Effect of Hong Huang Tang on memory enhancement and mitigation of microgravity-induced oxidative stress in C. elegans - Inam Ullah; Muhammad Zulqarnain Shakir; Xu Chen Zhou; Jixian Liu; Shilan Li; Huabiao Chen; Ning Jiang; Muhammad Wasim Usmani; Muhammad Qasim Barkat; Qiaobei Du; Yufen Zhao; Ning Wang; et al. (Biogerontology, 2026)

Protective effects of compound Gastrodia elata formula on the cognitive impairment induced by simulated weightlessness in mice - Fang Chen; Ning Jiang; Muhammad Noman Khan; Yiwen Zhang; Muhammad Zulqarnain Shakir; Guyue Zhou; Chenlu Xia; Yanfei Xu; Guanghua Lv; Mengzhou Xie; Xinmin Liu (Life Sciences in Space Research, 2026)

Synergistic effect of carbon nanotubes decorated spinel ferrites nanocomposite for robust photocatalytic degradation of persistent environmental pollutants - Sadaf Fatima; Bushra Shaheen; Norah Alomayrah; Noor ul Ain; Muhammad Ibrar; Muhammad Farooq Warsi; Imran Shakir (Journal of Water Process Engineering, 2025)

Standardizing Preoperative Care for Elective Spine Surgery: The University of Oklahoma Elective Spine Surgery Protocol - Lonnie Smith; David Barkyoumb; William C. Kaiser; Fauziyya Muhammad; Tara Sukut; Ishan Purani; Chao Li; DO; Karl Balsara; Hakeem J. Shakir; M. Burhan Janjua; John F. Burke; et al. (GeroScience, 2025)

Therapeutic innovations: targeting ROS production in AML with natural and synthetic compounds - Mohammed Hashim Mohammed; Raed Fanoukh Aboqader Al-Aouadi; Subasini Uthirapathy; Gaurav Sanghvi; Rekha M M; Resan Shakir Abdulamer; G. V. Siva Prasad; Mayank Kundlas; Fayzulla Khamraev; Muhammad Ikram Ullah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Correction: Emodin, a Potent Anthraquinone Mitigates MPTP-Induced Parkinsons’ Disease Pathology by Regulating Nrf2 and Its Downstream Targets: In Silico and In Vivo Approach - Sarwat Jahan; Muhammad Ikram; Sami Siraj; Shakir Ullah; Muhammad Zakria; Nasir Ahmad (Molecular Neurobiology, 2025)

Quantitative assessment of asymptomatic spinal cord compression using MRI: a multi-center study - Ali F. Khan; Sanaa Hameed; Alaa Baha; Fauziyya Muhammad; Grace Haynes; Amber Dastgir; Suresh K. Gulla; Hakeem J. Shakir; Michael L. Rohan; Yasin Y. Dhaher; Zachary A. Smith (GeroScience, 2025)

Molecular identification, risk factors’ assessment and phylogenetic analysis of Toxoplasma gondii in goats from Malakand Division, Khyber Pakhtunkhwa, Pakistan - Ahmad Irshad; Shumaila Noreen; Uswa Sajid; Muhsin Jamal; Muhammad Anwar Iqbal; Ubaid Ullah; Talat Sabtain; Shakir Ullah; Eliana Ibañez-Arancibia; Patricio R. De Los Ríos-Escalante; Hanène Belkahia; Mourad Ben Said; et al. (Veterinary Research Communications, 2025)

Probing the synergistic effect of MXene (TiCT) and MWCNTs on NiWO for superior water-splitting and supercapacitor studies - Amna Irshad; Mirza Mahmood Baig; Seung Goo Lee; Imran Shakir; Zeid A. ALOthman; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2025)

Microbial production and applications of glucose oxidase - Mehwish Sarfaraz; Dalia Sukmawati; Hafiz Abdullah Shakir; Muhammad Khan; Marcelo Franco; Muhammad Irfan (Systems Microbiology and Biomanufacturing, 2025)

Emodin, a Potent Anthraquinone Mitigates MPTP-Induced Parkinsons’ Disease Pathology by Regulating Nrf2 and Its Downstream Targets: In Silico and In Vivo Approach - Sarwat Jahan; Muhammad Ikram; Sami Siraj; Shakir Ullah; Muhammad Zakria; Nasir Ahmad (Molecular Neurobiology, 2025)

An integrated comprehensive approach describing structural features and comparative petrophysical analysis between conventional and machine learning tools to characterize carbonate reservoir: A case study from Upper Indus Basin, Pakistan - Zohaib Naseer; Urooj Shakir; Muyyassar Hussain; Qazi Adnan Ahmad; Kamal Abdelrahman; Muhammad Fahad Mahmood; Mohammed S. Fnais; Muhsan Ehsan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Molecular prevalence and genetic diversity of Hepatozoon canis in Rhipicephalus sanguineus s.l. and Hyalomma anatolicum infesting dogs - Hafiza Amna Bilal; Madiha Rasool; Arfa Bibi; Hira Muqaddas; Iqra Majeed; Muhammad Farooq; Kasim Sakran Abass; Samir Ibenmoussa; Turki M. Dawoud; Shakir Ullah; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Optimization and partial purification of tannase from Bacillus licheniformis AS1 under submerged fermentation and its application - Aqsa Shafique; Hafiz Abdullah Shakir; Muhammad Irfan; Shaukat Ali; Muhammad Khan; Chaman Ara; Noor Khan (Systems Microbiology and Biomanufacturing, 2025)

Reviewing the impact of seed-borne mycoflora on mycotoxin accumulation: A threat to lentil genetic resources - Sanam Asif; Momina Nisar; Shakir Ullah; Muhammad Naeem (Toxicon, 2025)

Theabrownin: a dietary nutraceutical with diverse anticancer mechanisms - Muhammad Faisal Maqbool; Sameena Gul; Muhammad Ishaq; Amara Maryam; Muhammad Khan; Hafiz Abdullah Shakir; Muhammad Irfan; Yongming Li; Tonghui Ma (Natural Product Research, 2025)

First report of Hepatozoon and Lankesterella spp. infections in wild rodents from Pakistan, and their potential impact on blood parameters and oxidative stress markers in vital organs - Maryam Ijaz; Asmat Ullah Khan; Muhammad Ali; Shakir Ullah; Muhammad Naeem; Samir Ibenmoussa; Turki M. Dawoud; Adil Khan; Mourad Ben Said; Furhan Iqbal (Veterinary Research Communications, 2025)

Maackiain: A comprehensive review of its pharmacology, synthesis, pharmacokinetics and toxicity - Waqas Haider; Wei Pan; Dayang Wang; Waqas Niaz; Muhammad Kashif Zaman; Raza Ullah; Shakir Ullah; Muhammad Rafiq; Bing Yu; Hailin Cong (Chemico-Biological Interactions, 2025)

The association of ABCB1 gene polymorphism with clinical response to carbamazepine monotherapy in patients with epilepsy - Haroon Ur Rashid; Shakir Ullah; Daniel F. Carr; Muhammad Ijaz Khan Khattak; Muhammad Imran Asad; Mujeeb Ur Rehman; Muhammad Khalid Tipu (Molecular Biology Reports, 2024)

Data-driven exploration in complex basins: A critical aspect of new prospect delineation in thin sands using simultaneous seismic inversion - Urooj Shakir; Aamir Ali; Muyyassar Hussain; Ahmed E Radwan; Ahmed Abd El Aal; Muhammad Raiees Amjad; Muhammad Fahad Mahmood (Journal of Earth System Science, 2024)

Evaluating machine learning approaches for aboveground biomass prediction in fragmented high-elevated forests using multi-sensor satellite data - Asim Qadeer; Muhammad Shakir; Li Wang; Syed Muhammad Talha (Remote Sensing Applications: Society and Environment, 2024)

Identifying thresholds of time-lag and accumulative effects of extreme precipitation on major vegetation types at global scale - Min Liu; Hao Wang; Huiliang Zhai; Xiaochong Zhang; Muhammad Shakir; Jianying Ma; Wei Sun (Agricultural and Forest Meteorology, 2024)

Optimization of protease production using Bacillus velezensis through response surface methodology and investigating its applications as stain remover - Humaira; Farah Deba; Hafiz Abdullah Shakir; Muhammad Khan; Marcelo Franco; Muhammad Irfan (Systems Microbiology and Biomanufacturing, 2024)

Synergy of zero-dimensional carbon dots decoration on the one-dimensional architecture of Ag-doped V2O5 for supercapacitor and overall water-splitting applications - Amna Irshad; Sonia Zulfiqar; Zeid A.Alothman; Imran Shakir; Muhammad Farooq Warsi; Eric W. Cochran (Fuel, 2024)

Energy, economic and environmental (3E) analyses of solar photovoltaic and fuel cell based hybrid energy system for a developing country: a worldwide approach to sustainable energy - Maham Fazal; Abdul Kashif Janjua; Mustafa Anwar; Muhammad Hassan; Sehar Shakir; Ali Bahadar (Environment, Development and Sustainability, 2024)

Sembar Formation as an Unconventional Prospect: New Insights in Evaluating Shale Gas Potential Combined with Deep Learning - Muhammad Raiees Amjad; Urooj Shakir; Muyyassar Hussain; Awais Rasul; Saqib Mehmood; Muhsan Ehsan (Natural Resources Research, 2023)

Degenerative cervical myelopathy: establishing severity thresholds for neuromotor dysfunction in the aging spine using the NIH Toolbox Assessment Scale - Fauziyya Muhammad; Sanaa Hameed; Grace Haynes; Esmaeil Mohammadi; Ali F. Khan; Hakeem Shakir; Zachary A. Smith (GeroScience, 2023)

The impact of CSR and green consumption on consumer satisfaction and loyalty: moderating role of ethical beliefs - Sohail Ahmad; Muhammad Irfan Shakir; Afshan Azam; Shahid Mahmood; Qingyu Zhang; Zaheer Ahmad (Environmental Science and Pollution Research, 2023)

Aspartame, a Synthetic Dipeptide Mediated Biochemical and Histopathological Alterations in Hepato-nephric Tissues of Mice and Pharmaceutical Intervention by Sesame Oil - Chaman Ara; Memoona Arshad; Shaukat Ali; Hafiz Abdullah Shakir; Muhammad Summer; Muhammad Khan; Iram Liaqat; Madeeha Arshad (International Journal of Peptide Research and Therapeutics, 2023)

Recent advances in green hydrogen production, storage and commercial-scale use via catalytic ammonia cracking - Muhammad Asif; Syeda Sidra Bibi; Sheraz Ahmed; Muhammad Irshad; Muhammad Shakir Hussain; Hassan Zeb; Muhammad Kashif Khan; Jaehoon Kim (Chemical Engineering Journal, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Retraction notice to “Melatonin rescues the mice brain against cisplatin-induced neurodegeneration, an insight into antioxidant and anti-inflammatory effects” [Neurotoxicology 87 (2021) 1–10] - Muhammad Zakria; Nasir Ahmad; Lina Tariq Al Kury; Abdullah Alattar; Zia Uddin; Sami Siraj; Shakir Ullah; Reem Alshaman; Muhammad Imran Khan; Fawad Ali Shah (NeuroToxicology, 2023)

Assessing the impact of green consumption behavior and green purchase intention among millennials toward sustainable environment - Madad Ali; Shakir Ullah; Muhammad Salman Ahmad; Mui Yee Cheok; Hamood Alenezi (Environmental Science and Pollution Research, 2022)

Gravity and electrical resistivity investigations to mark concealed seepage sources from Kanjoor Dam, Pakistan - Waqar Ali Zafar; Urooj Shakir; Rizwan Ahmed; Junaid Ahmed; Muhammad Younis Khan; Shamim Akhtar; Talat Iqbal (Arabian Journal of Geosciences, 2022)

Aging and its treatment with vitamin C: a comprehensive mechanistic review - Shumaila Mumtaz; Shaukat Ali; Hafiz Muhammad Tahir; Syed Akif Raza Kazmi; Hafiz Abdullah Shakir; Tafail Akbar Mughal; Samaira Mumtaz; Muhammad Summer; Muhammad Adeel Farooq (Molecular Biology Reports, 2021)

Implication of Remote Sensing Data under GIS Environment for Appraisal of Irrigation System Performance - Sultan Ahmad Rizvi; Afeef Ahmad; Muhammad Latif; Abdul Sattar Shakir; Aftab Ahmad Khan; Waqas Naseem; Muhammad Riaz Gondal (Water Resources Management, 2021)

Evaluation of sex steroid hormones and reproductive irregularities in diethyl phthalate-exposed premature mice: modulatory effect of raw honey against potential anomalies - Chaman Ara; Asmatullah; Faiza Yaseen; Shaukat Ali; Hafiz Abdullah Shakir; Muhammad Khan; Shagufta Andleeb; Nageena Ramzan (Environmental Science and Pollution Research, 2021)

Evaluation of Cadmium Chloride-Induced Toxicity in Chicks Via Hematological, Biochemical Parameters, and Cadmium Level in Tissues - Shaukat Ali; Saleha Bashir; Shumaila Mumtaz; Hafiz Abdullah Shakir; Chaman Ara; Farooq Ahmad; Hafiz Muhammad Tahir; Mehwish Faheem; Muhammad Irfan; Azeem Masih; Mazhar Ulhaq; Saiqa Andleeb (Biological Trace Element Research, 2021)

Correction to: Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Chemical composition of gemstones and characterization of their host pegmatites and country rocks from Chumar Bakhoor, Gilgit-Baltistan, Pakistan: implications for the source of gem-forming fluids - Amjad Hussain; Muhammad Tahir Shah; Mohammad Arif; Muhammad Hassan Agheem; Muhammad Saleem Mughal; Shakir Ullah; Syed Asim Hussain; Izhar Sadiq (Arabian Journal of Geosciences, 2021)

Implications of Solid Lipid Nanoparticles of Ganoderic Acid for the Treatment and Management of Hepatocellular Carcinoma - Mahfoozur Rahman; Sarwar Beg; Khalid S. Alharbi; Nabil K. Alruwaili; Nasser Hadal Alotaibi; Abdulaziz I. Alzarea; Waleed H. Almalki; Sattam Khulaif Alenezi; Waleed M. Altowayan; Mohammed S. Alshammari; Muhammad Afzal; Shakir Saleem; et al. (Journal of Pharmaceutical Innovation, 2021)

Assessment of Real Time, Multi-Satellite Precipitation Products under Diverse Climatic and Topographic Conditions - Muhammad Masood; Abdul Sattar Shakir; Aftab Hussain Azhar; Guhlam Nabi; Habib-u-Rehman (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Cardiac toxicity of heavy metals (cadmium and mercury) and pharmacological intervention by vitamin C in rabbits - Shaukat Ali; Zubia Awan; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Siddique Awan; Saima Sharif; Muhammad Irfan; Muhammad Adeeb Khan (Environmental Science and Pollution Research, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Dose and duration-dependent toxicological evaluation of lead acetate in chicks - Saeeda Hussain; Shaukat Ali; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Hafiz Muhammad Tahir; Mazhar Ulhaq; Muhammad Adeeb Khan; Muhammad Tariq Zahid (Environmental Science and Pollution Research, 2020)

The role of garlic oil in the amelioration of oxidative stress and tissue damage in rohu Labeo rohita treated with silver nanoparticles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Wajid; Sabeen Sabri; Muhammad Shakir (Fisheries Science, 2020)

Therapeutic role of garlic and vitamins C and E against toxicity induced by lead on various organs - Shumaila Mumtaz; Shaukat Ali; Rida Khan; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Samiara Mumtaz; Saiqa Andleeb (Environmental Science and Pollution Research, 2020)

Toxicological effects of toxic metals (cadmium and mercury) on blood and the thyroid gland and pharmacological intervention by vitamin C in rabbits - Rida Khan; Shaukat Ali; Shumaila Mumtaz; Saiqa Andleeb; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Khalil Ahmad Khan; Muhammad Adeeb Khan; Hafiz Abdullah Shakir (Environmental Science and Pollution Research, 2019)

The protective role of ascorbic acid in the hepatotoxicity of cadmium and mercury in rabbits - Shumaila Mumtaz; Shaukat Ali; Rida Khan; Saiqa Andleeb; Mazhar Ulhaq; Muhammad Adeeb Khan; Hafiz Abdullah Shakir (Environmental Science and Pollution Research, 2019)

Modeling Sugar Beet Response to Different Combinations of On-Farm Water Management Practices Under Semi-arid Sub-tropical Environment - Abdul Malik; Abdul Sattar Shakir; Muhammad Jamal Khan; Muhammad Ajmal; Muhammad Shahzad Khattak; Taj Ali Khan; Zia Ul Haq; Mahmood Alam Khan; Naeem Ijaz (Sugar Tech, 2019)

Renal toxicity of heavy metals (cadmium and mercury) and their amelioration with ascorbic acid in rabbits - Shaukat Ali; Sidra Hussain; Rida Khan; Shumaila Mumtaz; Nasra Ashraf; Saiqa Andleeb; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Muhammad Khalil Ahmad Khan; Mazhar Ulhaq (Environmental Science and Pollution Research, 2019)

Detection of mineral alteration induced by hydrocarbon microseepages by using remotely sensed data in the Fateh Jang area of the Northern Potwar region of Pakistan - Ayesha Habib; Muhammad Khubaib Abuzar; Ijaz Ahmad; Urooj Shakir; Syed Amer Mahmood; Mumtaz Ali Khan; Muhammad Fahad Mahmood (Arabian Journal of Geosciences, 2019)

Performance Evaluation of the Raised-Bed Planting and Potential in Improving Sugar Beet Yield and Water Use Efficiency in Pakistan - Abdul Malik; Abdul Sattar Shakir; Muhammad Latif; Muhammad Ajmal (Sugar Tech, 2018)

Pesticide-induced oxidative stress and antioxidant responses in tomato (Solanum lycopersicum) seedlings - Shakirullah Khan Shakir; Shahid Irfan; Basreen Akhtar; Shafiq ur Rehman; Muhammad Khan Daud; Nadia Taimur; Azizullah Azizullah (Ecotoxicology, 2018)

Oxyphenbutazone promotes cytotoxicity in rats and Hep3B cellsvia suppression of PGE2 and deactivation of Wnt/β-catenin signaling pathway - Shakir Saleem; Ruqaiyah Khan; Muhammad Afzal; Imran Kazmi (Molecular and Cellular Biochemistry, 2018)

Ecotoxicological evaluation of two anti-dandruff hair shampoos using Lemna minor - Azizullah Azizullah; Shakirullah Khan Shakir; Shahana Shoaib; Halima Bangash; Nadia Taimur; Waheed Murad; Muhammad Khan Daud (Environmental Monitoring and Assessment, 2018)

Prediction of river bank erosion and protection works in a reach of Chenab River, Pakistan - Muhammad Ashraf; Abdul Sattar Shakir (Arabian Journal of Geosciences, 2018)

Assessment of AquaCrop Model in Simulating Sugar Beet Canopy Cover, Biomass and Root Yield under Different Irrigation and Field Management Practices in Semi-Arid Regions of Pakistan - Abdul Malik; Abdul Sattar Shakir; Muhammad Ajmal; Muhammad Jamal Khan; Taj Ali Khan (Water Resources Management, 2017)

River bank erosion and channel evolution in sand-bed braided reach of River Chenab: role of floods during different flow regimes - Muhammad Ashraf; Muhammad Tousif Bhatti; Abdul Sattar Shakir (Arabian Journal of Geosciences, 2016)

Optimization of Multiple Reservoirs Operation with Consideration to Sediment Evacuation - Muhammad Usman Rashid; Abdul Sattar Shakir; Noor Muhammad Khan; Abid Latif; Muhammad Mubashir Qureshi (Water Resources Management, 2015)

Seasonal abundance of soil arthropods in relation to meteorological and edaphic factors in the agroecosystems of Faisalabad, Punjab, Pakistan - Muhammad Mussadiq Shakir; Sohail Ahmed (International Journal of Biometeorology, 2015)

Microbial contamination of drinking water in Pakistan—a review - Farhat Nabeela; Azizullah Azizullah; Roqaia Bibi; Syeda Uzma; Waheed Murad; Shakirullah Khan Shakir; Waheed Ullah; Muhammad Qasim; Donat-Peter Häder (Environmental Science and Pollution Research, 2014)

LONG‐TERM EFFECTIVENESS OF LINING TERTIARY CANALS IN THE INDUS BASIN OF PAKISTAN - Ali Raza; Muhammad Latif; Abdul Sattar Shakir (Irrigation and Drainage, 2013)
This study was conducted to determine the effectiveness of lining tertiary canals with respect to their lining age. Twenty partially lined canals (1–25 years of lining age) were randomly selected and these were classified into five age groups with a class interval of 5 years. The flow rate of each selected channel was measured at the head and tail of the lined sections, and in the unlined sections at a distance equal to the length of the lined sections. The conveyance losses varied from 0.76 to 1.31 l s ‐1 per 100 m length. The lowest losses were observed in the newly lined canals (1– 5 years old) while the highest losses were observed in the case of group IV, having a lining age of between 16 and 20 years. The conveyance losses were reduced by 47 and 30% respectively in groups I and V. Thus, these results clearly demonstrate that the effectiveness of lining decreases with its age. A significant amount of water is saved by the newly lined canals; however, this benefit decreases as the lining become older. Copyright © 2013 John Wiley & Sons, Ltd.

Characterization of tannery effluent wastewater by proton-induced X-ray emission (PIXE) analysis to investigate their role in water pollution - Lubna Shakir; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2012)